The Role of T.V. Shaws in Transmitting Violence in Children: An Analytic Study for T.V. Chanels for Children During 1/3/2014 – 1/9/2014: يوسف محمد حسين (Al-Academy, 2016)
Our study comes up to clarify the role of television in spreading the culture of violence with a child. This study represents one of the important studies that have tried to highlight the impact of these programmes, particularly cartoons, on the child's behaviors, actions and acquired habits.Violence considers a common phenomenon among the people, as the role of the media, particularly TV has a vital role due to its properties, characteristics and its significant impact on different segments and groups in society and in children particularly through exposure to programmes of films.The results of the study have been affected by the rising proportion of females to males, and that the contribution of real life has a big role in the child acquisition of violent behavior which comes effectively through the children's imitation of the evil characters in their work as well as the use of violence in the street or at home or even at school, as well as not to comply with the orders of the parents .In addition, this study has highlighted the increasing of the negative effects (socially) of the TVdubbed programmes on the child to develop of the candied , food, and conducts of the Western lifestyle and dissemination these values .Beside the psychological effects such as making the child a heartless and exacerbate the fear and panic, the child's physical damage effects have their own effect on the child which is embodied in the incidence of insomnia for the child and prejudice sleep system which makes himno sleep long hours.